Detailed analysis of coke precursor formation in catalytic perhydro benzyltoluene dehydrogenation processes - Henseler, Julian; Schärfe, Timo; Steffen, Julien; Görling, Andreas; Geißelbrecht, Michael; Wasserscheid, Peter (Fuel, 2025)
Fuel-like handling, good hydrogen storage capacity and low-pressure operations for charging (at <8 bar) and discharging (at <5 bar) make Liquid Organic Hydrogen Carrier (LOHC) systems an interesting option for hydrogen storage and transport in a future hydrogen economy. One important aspect of all LOHC technologies is the long-term use of the carrier material in many repetitive storage cycles. This requires a minimization of side product formation in all process steps involved. Heavy-boiling side products are in addition problematic as they may remain on the catalyst in gas phase dehydrogenation reactions, where they are converted into coke, which blocks the active sites of the catalyst. In contrast, in liquid phase LOHC dehydrogenation processes, high boiling side products are washed off the catalyst surface and are found dissolved in the LOHC mixture. This enables their analytical identification and quantification. A more detailed understanding of the coke precursor formation enables the development of LOHC purification processes and can give access to a knowledge-based optimization of the applied catalyst materials or process conditions. In this study we present a multi-instrumental analytic approach (GC-FID, HPLC-DAD, HRMS, NMR) to study in detail high-boiler formation in the liquid phase dehydrogenation of perhydro benzyltoluene (H12-BT) under purposely applied very harsh conditions. Our work reveals the structure of so far unidentified side products and gives new insight into the mechanism of high-boiler formation on a commercial Pt on alumina dehydrogenation catalyst.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Benzyltoluene; Chromatography; High resolution mass spectrometry petroleomics; Hydrogen; LOHC